GITSIGHT PRO: Herramienta para el análisis de repositorios públicos (2024)
This project focuses on developing a comprehensive tool for analyzing productivity in software development environments, specifically targeting public GitHub repositories. It provides metrics to facilitate the analysis and comparison of teams effectiveness and efficiency over different time periods, based on user contributions.